2016
DOI: 10.5572/kosae.2016.32.1.021
|View full text |Cite
|
Sign up to set email alerts
|

Variation of OC and EC in PM<sub>2.5</sub> at Mt. Taehwa

Abstract: . While OC showed greater seasonal variation, the diurnal variation was more noticeable for EC through all seasons with a clear maximum in the morning, which reveals the influence of vehicle emissions. In contrast, OC exhibited a broad second peak in the afternoon during May~June, when biological activities were the highest. Using the morning peaks of EC and OC, primary OC/EC ratio was assessed, which was assumed to be anthropogenic origin. It was the greatest in winter followed by spring and the lowest in wet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
3
0
1
Order By: Relevance
“…In the previous study, vehicle emissions from nearby roads have been identified as main sources for EC at TRF (Ham et al, 2016). In contrast, OC was dominated by contemporary sources with Fc (OC) of 897% (n=2), albeit the small number of samples (n=2).…”
Section: Fm For Ec and Ocmentioning
confidence: 92%
See 1 more Smart Citation
“…In the previous study, vehicle emissions from nearby roads have been identified as main sources for EC at TRF (Ham et al, 2016). In contrast, OC was dominated by contemporary sources with Fc (OC) of 897% (n=2), albeit the small number of samples (n=2).…”
Section: Fm For Ec and Ocmentioning
confidence: 92%
“…In summer, the average NOx was low at TRF (Ham et al, 2016) as well as China (Wang et al, 2007). In contrast, NH3 levels were the highest across China (Pan et al, 2018).…”
Section:  15 N For Tnmentioning
confidence: 95%
“…대기 중의 초미세먼지는 직접적으로 흡수 또는 산란 을 통해 시정에 영향을 주며 가시도를 저하시키고 구 름 응결핵으로 작용하면서 기후변화를 초래한다 (Gao et al, 2015;Rastogi et al, 2014;Tao et al, 2014 (Tang et al, 2017;Chen et al, 2016). 국내에서는 초미세먼지를 규제하기 위해 2015 년에 대기환경기준 (PM 2.5 50 μg/m 3 )을 도입하였으며 2018년 현재 초미세먼지 규제 기준은 35 μg/m 3 으로 강 화되었다 (Park et al, 2017;Ham et al, 2016 (Nowak et al, 2013;Kim et al, 2012;Lee et al, 2008). (Pathak et al, 2009).…”
Section: 서 론unclassified
“…The diagram of (a) PILS-TOC and (b) PILS-IC at Bukhansan National Park (adapted fromPark et al, 2016).…”
mentioning
confidence: 99%